2016
DOI: 10.14814/phy2.12760
|View full text |Cite
|
Sign up to set email alerts
|

PlanHab: Hypoxia counteracts the erythropoietin suppression, but seems to exaggerate the plasma volume reduction induced by 3 weeks of bed rest

Abstract: The study examined the distinct and synergistic effects of hypoxia and bed rest on the erythropoietin (EPO) concentration and relative changes in plasma volume (PV). Eleven healthy male lowlanders underwent three 21‐day confinement periods, in a counterbalanced order: (1) normoxic bed rest (NBR; PIO 2: 133.1 ± 0.3 mmHg); (2) hypoxic bed rest (HBR; PIO 2: 90.0 ± 0.4 mmHg, ambient simulated altitude of ~4000 m); and (3) hypoxic ambulation (HAMB; PIO 2: 90.0 ± 0.4 mmHg). Blood samples were collected before, durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 51 publications
(111 reference statements)
5
16
0
Order By: Relevance
“…In the present study, the respiratory impairment observed in H-AMB at the fibre level did not translate into a functional impairment in vivo during small muscle mass exercise, as also observed in the study by Calbet et al 2009. It can be hypothesized that this observation, together with the absence of further functional impairments following H-BR, compared to N-BR, could be attributed, at least in part, to the increased blood [Hb] occurring in hypoxia (Keramidas et al 2016b).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In the present study, the respiratory impairment observed in H-AMB at the fibre level did not translate into a functional impairment in vivo during small muscle mass exercise, as also observed in the study by Calbet et al 2009. It can be hypothesized that this observation, together with the absence of further functional impairments following H-BR, compared to N-BR, could be attributed, at least in part, to the increased blood [Hb] occurring in hypoxia (Keramidas et al 2016b).…”
Section: Discussionsupporting
confidence: 70%
“…Such a stimulus is sufficiently severe to induce a down‐regulation of the oxidative processes inside the skeletal muscle (Horscroft & Murray, ) and a significant erythropoietin response, as indeed demonstrated by Keramidas et al . () in the same subjects of the present study.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Bodkin et al 2006), information pertaining to the interactive effects of reduced loading of musculoskeletal and cardiovascular functions and hypoxia on working capacity is relatively scarce. The response was attributable to attenuated convective O 2 transport, as indicated by the lower peak cardiac output, secondary to a more pronounced bedrest-driven hypovolaemic reaction in hypoxia (Loeppky et al 1993;Keramidas et al 2016b). The response was attributable to attenuated convective O 2 transport, as indicated by the lower peak cardiac output, secondary to a more pronounced bedrest-driven hypovolaemic reaction in hypoxia (Loeppky et al 1993;Keramidas et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Specific data related to appetite , insulin sensitivity , bone health (Rittweger et al, 2016), hematology (Keramidas et al, 2016b), peak oxygen uptake (Keramidas et al, 2016a), and skeletal muscle miRNA expression (Rullman et al, 2016), are available elsewhere.…”
Section: Methodsmentioning
confidence: 99%